Multi-Level Risk and Protective Factors for Substance Use Among Zambian Street Youth. (6th June 2016) - Tyler, Kimberly A.; Handema, Ray; Schmitz, Rachel M.; Phiri, Francis; Kuyper, Kourtney S.; Wood, Charles
ABSTRACT: Background : High rates of substance use have been reported among youth in Zambia. This is particularly concerning given that substance use is one of the biggest risk factors placing young people at risk for HIV infection. Objectives: The purpose of the current study is to examine how multi-level risk and protective factors (i.e., community, family, peers, individual) influence alcohol and marijuana use. Methods : A total of 250 street youth in Lusaka, Zambia were interviewed in the summer of 2014 about their alcohol and marijuana use and reasons for usage. Data were analyzed using descriptive and multivariate methods. Results : Youth reported high rates of alcohol use. At the multivariate level, peer and individual level variables (e.g., using alcohol or drugs for coping or for fun) explained the most variance, followed by family level factors. Community level variables explained the least variance in all models. Conclusion/Importance : A better understanding of multi-level risk and protective factors for young people's alcohol and marijuana use could lead to the development of better intervention strategies to reduce this behavior among Zambian street youth.